Antibacterials in Aquatic Environment and Their Toxicity to Fish - Bartosz Bojarski; Barbara Kot; Małgorzata Witeska (MDPI AG, 2020)
Antibacterial agents are commonly present in aquatic environment at low concentrations. Terrestrial animal farms, human medicine and aquaculture are main sources of water contamination with antibacterials. Antibiotics were proved to be directly toxic to fish causing oxidative stress, general stress response, histopathological lesions, hematological, metabolic, and reproductive disorders, as well as immunosuppressive and genotoxic effects. Environmentally realistic low concentrations of antibiotics also disturb aquatic bacterial communities causing alterations in fish symbiotic microbiota and induce emergence of antibiotic-resistant pathogenic bacteria by exerting selective pressure on spread of antibiotic-resistance genes.